DESIGN OF INNER LID OF PRESSURE COOKER WITH CIRCULAR SHAPE HAVING STRAIGHT EDGES - Prof. Date D. D.; Dr. R. G. Tated (International Journal of Innovations in Engineering Research and Technology, 2021)
Pressure cooker works hand in hand with the working woman. This is happening because of saving in time & energy. It means that pressure cooker become the inevitable item in kitchen. If we concentrate on the analysis of inner lid of the pressure cooker, it is highly beneficial for everyone. That is why we concentrate on the possible shapes of lids of pressure cooker. The existing pressure cooker is of two type i. e. inner lid and outer lid type. The shape of existing inner lid pressure cooker is generally having elliptical shape. This shape is because of locking & easy handling. The different alternatives are arising. Out of which the best alternative found is the circular shape having straight edges at the edges. The modification suggested here is also serving the same purposes as like the previous one.